Design of Temperature Control System on UV Weathering Chamber Based on PID - Zakaria, Zakaria; Romahadi, Dedik; Fitri, Muhamad (Universitas Mercu Buana, 2023)
The influence of high temperature and exposure to ultraviolet (UV) radiation from sunlight, rain, and humidity causes damage to the composite material and consequently, reduces its mechanical performance. Weathering experiments can be carried out outdoors or under laboratory conditions. Material degradation tests can be carried out directly using natural conditions or laboratory test equipment that artificially simulates natural conditions. An automatic temperature control system is needed to keep the setpoint stable during the degradation test. The controller on the system uses Arduino based on Proportional, Interval, and Derivative (PID). The test was carried out by running the system with different PID parameter values three times to obtain the most optimize-tingling results in maintaining the setpoint at steady state conditions. Based on the results of tests that have been carried out with a setpoint of 40⁰C, the most optimal results are obtained with values of Kp=10, Ki=20, and Kd=30. The average temperature is 40.02⁰C with an average error percentage of 2% and an average accuracy rate of 98%.